Village Head Election System Based on SBT Regency Regulation Number 5 of 2017 - Hulihulis, Firdaus; Purnama, Bayu; Kariadi, Kariadi (Journal of Law Justice (JLJ), 2025)
This study aims to analyze the implementation of village head elections in Lalasa Administrative Village, Pulau Panjang Subdistrict, East Seram Regency, by examining its compliance with legal provisions, particularly Law Number 6 of 2014, Minister of Home Affairs Regulation Number 112 of 2014, and Regional Regulation Number 5 of 2017. The research approach uses a qualitative method with primary data sources through field observations and in-sdepth interviews with relevant parties, as well as secondary data through literature review. The analysis is conducted using a descriptive-qualitative approach to describe the factual conditions and compare them with the applicable legal norms. The novelty of this research lies in its focus on the gap between formal legal procedures and customary practices in the election of village heads, which is rarely discussed specifically in the context of administrative villages in the Maluku region. The results show that although some formal stages, such as the formation of an election committee, have been carried out in accordance with the rules, the practice of appointing village heads in Lalasa Village is still dominated by customary mechanisms in the form of direct appointment based on lineage without voting. This has resulted in limited political participation of the community and the potential for a decline in the legitimacy of village leadership. In conclusion, harmonization between positive law and customary law is necessary so that village administration can be carried out democratically, transparently, and in accordance with regulations, while still respecting local wisdom.